Mycotoxins, a problematic affecting food safety in food industry for pets worldwide - Boncompagno, Nadia (2021)
The feeding of companion animals has some objectives of its own that differentiate it from that of other animals. In addition of providing a correct and balanced amount of nutrients, it should allow them to optimize their health, activity and longevity, since these are often considered as “family members” and are treated as such. Through different investigations it has been shown that the pet food can be contaminated with mycotoxins. These metabolites are produced by different fungal species which contaminate cereals and their derivatives, used as raw materials for the manufacture of these products. This has greatly favoured the risk of poisoning with these substances. Therefore, the pet food industry must ensure that the concentration of mycotoxins in its products remains below the established toxicological limits. It is known that the different stages of the pet food production process, cannot completely inactivate these fungal metabolites, so the best way to avoid contamination with fungal toxins is through prevention, however, it is often insufficient. Several alternatives have been sought to treat the contaminated grain. One of the most promising approaches to solve this problem is the addition of adsorbents materials, such as clay materials, activated carbon and yeast cell wall extracts. It should be noted that all these practices do not replace the need to use highquality ingredients, from trusted suppliers, with established processing guidelines to avoid the production of mycotoxins.